Implementasi Pemberian Hak Restitusi Oleh Pelaku Kepada Korban Kekerasan Seksual - Christina Febri Silalahi; Esa Nur Hakam; Goldman Mediyana; Nabiella Putri Nastiti; Herli Antoni (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
This study aims to reinforce the implementation of material and formal law in a crime of sexual violence, in terms of granting restitution from the perpetrator to the victim for his actions, providing legal protection and utilizing criminal law in the trap of a crime of sexual violence. Restitution as referred to in this study is the provision of material from the perpetrator to the victim for his crime because he committed sexual violence which caused the victim to experience physical and psychological suffering, to restore the condition and condition of the victim after the crime, the perpetrator must provide restitution to the victim, the amount of restitution determined by court ruling. In protecting victims of sexual violence to avoid all forms of threats and intimidation, Indonesia has institutions to carry out their obligations. Namely, through the Witness and Victim Protection Agency whose duties, functions and authorities have been granted in accordance with the law. This aims to protect victims who are very vulnerable to all forms of threats and intimidation. Legal protection was also given before the crime occurred, namely by Law no. 12 of 2022 concerning Crimes of Sexual Violence, Law no. 35 of 2014 concerning Amendments to Law no. 23 of 2002 concerning Child Protection, and Law no. 23 of 2004 concerning the Elimination of Domestic Violence. Someone who commits a crime of sexual violence will receive legal consequences, in the form of imprisonment, fines, and restitution to the victim, the amount of which is determined by the court. However, if restitution is insufficient, the State is obliged to provide compensation to the victim for the lack of restitution given to the victim.